Prime and pull of T cell responses against cancer-exogenous antigens is effective against CPI-resistant tumors - Fulvia Troise; Guido Leoni; Emanuele Sasso; Mariarosaria Del Sorbo; Marialuisa Esposito; Giuseppina Romano; Simona Allocca; Guendalina Froechlich; Gabriella Cotugno; Stefania Capone; Antonella Folgori; Elisa Scarselli; et al. (Molecular Therapy: Oncology)
Neoantigen (neoAg)-based cancer vaccines expand preexisting antitumor immunity and elicit novel cancer-specific T cells. However, at odds with prophylactic vaccines, therapeutic antitumor immunity must be induced when the tumor is present and has already established an immunosuppressive environment capable of rapidly impairing the function of anticancer neoAg T cells, thereby leading to lack of efficacy. To overcome tumor-induced immunosuppression, we first vaccinated mice bearing immune checkpoint inhibitor (CPI)-resistant tumors with an adenovirus vector encoding a set of potent cancer-exogenous CD8 and CD4 T cell epitopes (Ad-CAP1), and then “taught” cancer cells to express the same epitopes by using a tumor-retargeted herpesvirus vector (THV-CAP1). Potent CD8 effector T lymphocytes were elicited by Ad-CAP1, and subsequent THV-CAP1 delivery led to a significant delay in tumor growth and even cure.